Uji validitas dan praktikalitas modul fisika bermuatan literasi baru materi fluida untuk meningkatkan hasil belajar siswa kelas XI SMAN 6 Padang - Shintya Ruci Pratama; Asrizal A; Fatni Mufit; Wahyuni S.D (Universitas Negeri Padang, 2020)
The 21st Century is marked by the progress of Science and Technology which is developing rapidly. The 2013 curriculum is one of the government's efforts to answer the challenges of the 21st century. Learning demands in the 2013 curriculum are student-centered learning, integrating literacy, and independence of students in learning. A new reality that hasn't been done well. The solution to overcome this problem is the use of new physics literacy modules. The purpose of this research is to determine the validity and practicality of using new physics literacy modules. This type of research was Research and Development (R&D). The object of research was a new physics module containing literacy in fluid material. The instrument to validate this module was the questionnaire sheet on the validity test. The questionnaire sheet on the validity test consists of four components, namely the appropriateness of content, presentation, linguistics, and graphics. The validator to approve the validation of the physics module consisted of three physics lecturers from the Faculty of Mathematics and Natural Sciences UNP. The instrument to test this practical module was the questionnaire sheet on the practicality test. The questionnaire sheet on the practicality test consists of four components, which are easy to use, attractiveness, clarity and benefits. The physics module practitioners consisted of two physics teachers and thirty-five students of class XI IPA 3 at SMA N 6 Padang. The data analysis technique was descriptive statistics. Based on the analysis of the data, it can be concluded that the average value of the validity component of the physics module containing the new literacy is 89.35 categorized very well. For the average value of the practicality component according to the teacher is 80,48 and practicality according to students is 83.13 in the excellent category. Thus, the average value of the validation and practical physics modules in new literal fluid can be categorized into excellent categories.